Utilização da cinza de folha de cana-de-açúcar como material pozolânico em matrizes cimentantes - Moraes, João Cláudio Bassan de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Portland cement is widely used in building construction, and one of the mostly materials used in the world. However, Portland cement production generates huge amount of CO 2, and, consequently, researches for alternative materials in building construction is growing up. Another problem is related to growth of sugarcane production in Brazil. Sugar cane straw is a byproduct of harvesting sugar cane, and one of its qualities is the calorific value for power generation that can be compared to sugar cane bagasse. However, the production of energy from burning sugar cane straw generates a waste, the sugar cane straw ash. The residue is the maing element in this work, aiming its use as pozzolanic material in cementitious binder replacing partially the Portland cement. In this work, is studied since the production of this ash until this use in cementing matrices. First, the method of obtaining a good ash with pozzolanic qualities is studied. Therefore, furnaces are used to burn the straw and obtain the ash, then it passes through sieves, and finally grinding the material. After obtaining the ash, it is characterized from Chemical Composition, X-Ray Diffraction, Particle Size, Fourier Transform Infrared Spectroscopy, Thermogravimetric Analysis and Scanning Electron Microscopy. Then, after characterizing the ash, it is assessed in cement pastes/pozzolan and lime/pozzolan to evaluate their pozzolanic reactivity. Fourier Transform Infrared Spectroscopy, Thermogravimetric Analysis and Scanning Electron Microscopy are used to evaluate the development of pozzolanic reaction. Finally, the ash is used in mortars replacing partially in mass the Portland cement to evaluate the mechanical properties. Four different substitutions were assessed and were compared to the control with no sugarcane straw ash. Results from characterization of sugar cane straw ash and pastes, as well as mechanical properties of mortars, show ...

O cimento Portland é largamente utilizado na construção civil, sendo também um dos materiais mais utilizados do mundo. Porém, há uma grande emissão de CO 2 na produção do cimento Portland, então surge a busca por materiais alternativos na construção civil. Outro problema está relacionado com o crescimento da produção de cana-de-açúcar no Brasil. A folha de cana-de-açúcar é um subproduto da colheita da cana-de-açúcar, e ela possui como qualidade o seu poder calorífico para geração de energia, que é comparável ao do bagaço de cana-de-açúcar. Entretanto, a produção de energia a partir da queima da folha de cana-de- açúcar gera um resíduo, a cinza de folha de cana-de-açúcar. Este resíduo é o principal elemento deste trabalho, objetivando seu uso como material pozolânico em matrizes cimentantes substituindo parcialmente o cimento Portland. Neste trabalho, é estudado desde a produção desta cinza até a sua utilização em matrizes cimentantes. Primeiramente, é estudado o modo de obtenção de uma cinza com boas qualidades pozolânicas. Portanto, são utilizados fornos para queimar a folha e obter a cinza, depois esta passa por um processo de peneiramento e, finalmente, a moagem do material. Após obter a cinza, esta é caracterizada pela Composição Química, Difração de Raio-X, Granulometria, Espectroscopia de Infravermelho por Transformada de Fourier, Análise Termogravimétrica e Microscopia Eletrônica de Varredura. Em seguida, após a caracterização de cinza, esta é aplicada em pastas de cal/pozolana e cimento/pozolana com o objetivo de analisar sua reatividade pozolânica. Ensaios de Espectroscopia de Infravermelho por Transformada de Fourier, Análise Termogravimétrica e Microscopia Eletrônica de Varredura são utilizados como análise da evolução da reação pozolânica. Finalmente, a cinza é aplicada em argamassas substituindo parcialmente em massa...
Keywords: Cana-de-açúcar - Subprodutos; Materiais de construção; Pozolanas; Concreto - Mistura; Resistencia de materiais; Sustentabilidade; Concrete -- Moisture